Archival Management in the Postgraduate Program of Universitas Negeri Makassar - Jamaluddin Jamaluddin; Marwa Marwa; Nasir Nasir (Asha Publishing, 2024)
The presence of archives in the office has an important role in supporting the smooth work of employees This research aims to find out the governance of archives in the Postgraduate Program of the State University of Makassar. This research is qualitative, therefore to achieve the research objectives, data collection techniques are used, namely observation/observation, interviews and documentation with 3 informants, namely the Head of Administration and archival employees at the Postgraduate Program of Universitas Negeri Makassar. The results of the study show that archival governance in the Postgraduate Program of Universitas Negeri Makassar using four indicators, namely, 1) receipt and recording of archives is carried out by classifying documents based on each study program and for recording archives is carried out manually and also classified based on education level, 2) archive storage is carried out by entering into a bundle folder based on each study program After that, it is put into the filing cabinet, 3) Archive maintenance is carried out after four years of graduation or the student judiciary period. The maintenance of archives to remain authentic is by checking or reviewing documents or files that have been saved and then saving the documents in a folder folder, and 4) shrinkage and destruction of archives is carried out by employees after the four-year student judiciary period, archives that have expired will be taken down to the warehouse or given to the cleaning service for weighing. The supporting factor in archive management is the cooperation between employees so that work related to archives can be completed quickly. Meanwhile, the inhibiting factor is that there has not been an archive destroyer/destroyer so that the archives that are due to be destroyed are only given to the cleaning service to be weighed. In this study, using several latest indicators that can answer the formulation of research problems ranging from the stage of receiving and recording archives to shrinking and destroying archives in the Postgraduate Program of Universitas Negeri Makassar. The results of the study revealed several supporting factors and inhibiting factors in archival governance at the Postgraduate Program of Universitas Negeri Makassar in depth